2010
DOI: 10.1021/ie100840z
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Fluid-Dynamic Analysis To Improve the Mass Transfer Performances of Pd−Ag Membrane Modules for Hydrogen Purification

Abstract: This work is aimed at investigating the impact of the fluid flow features on the behavior of gas separation membrane modules. The investigation is carried out by particle image velocimetry (PIV) experiments and computational fluid dynamics (CFD) simulations. The experimental velocity data collected in a laboratory scale membrane module confirm the reliability of the gas velocity field calculated numerically solving the Navier-Stokes equations by a general-purpose finite volume CFD code, and the effect of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…The CFD methods have been applied to the simulation of separation of gas from the gas mixture only in a few cases [12,[20][21][22]. So far the CFD application to these membranes modeling study gives promising results, thus adopting CFD methodology for design and optimization of ion transport membranes for oxy-combustion power generation technologies.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…The CFD methods have been applied to the simulation of separation of gas from the gas mixture only in a few cases [12,[20][21][22]. So far the CFD application to these membranes modeling study gives promising results, thus adopting CFD methodology for design and optimization of ion transport membranes for oxy-combustion power generation technologies.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…The steady-state 2D CFD model employed in our study is based on the previously reported CFD models [26,27,34]. We assume a pseudo-homogeneous description of the catalytic bed [22,29], therefore the computational domain representing the catalytic packed bed is solved as a continuum.…”
Section: Model Equationsmentioning
confidence: 99%
“…Goto et al [28] studied H 2 permeation rate through a composite membrane with a Pd film coated on a porous ceramic tube and defined a numerical model based on the combined resistances of the Pd film and the composite support. Coroneo et al [26,27] investigated mass transfer characteristics of PdeAg membrane H 2 separation modules experimentally and numerically using Computational Fluid Dynamics (CFD). Though porous ceramic membranes provide higher permeabilities, dense Pd membranes perform much better in SMR due to their exceptional selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Given this situation, the concentration variation in radial direction (or concentration polarisation phenomena) is very weak as discussed elsewhere [9][10][11][12][13]. Therefore, we assume there was negligible concentration variation in the radial direction.…”
Section: Gas Phase Mass Transfermentioning
confidence: 99%
“…Literature related to gas separation on this topic is generally limited, whilst the majority of Computational Fluid Dynamic (CFD) investigations have focused on liquid separation [8]. To date, CFD simulation has been carried out for molecular sieve silica [9,10], Pd [11] and polymeric [12] membranes. These studies showed the significant benefit of distributed-parameter simulation in modelling membrane gas separation processes, thus replacing the averaged or ''lumped'' parameter model.…”
Section: Introductionmentioning
confidence: 99%